Mentoring the working nurse: a scoping review - Jerilyn Hoover; Adam D. Koon; Erica N. Rosser; Krishna D. Rao (BMC, 2020)
Abstract Background Mentoring programs for nurses already in the health workforce are growing in importance. Yet, the settings, goals, scale, and key features of these programs are not widely known. Objective To identify and synthesize research on in-service nurse mentoring programs. Methods We reviewed nurse mentoring research from six databases. Studies either referred explicitly to in-service nurse mentoring programs, were reviews of such programs, or concerned nurse training/education in which mentoring was an essential component. Results We included 69 articles from 11 countries, published from 1995 to 2019. Most articles were from high-income countries (n = 46) and in rural areas (n = 22). Programs were developed to strengthen clinical care (particularly maternal and neonatal care), promote evidence-based practice, promote retention, support new graduate nurses, and develop nurse leaders. Of the articles with sufficient data, they typically described small programs implemented in one facility (n = 23), with up to ten mentors (n = 13), with less than 50 mentees (n = 25), meeting at least once a month (n = 27), and lasting at least a year (n = 24). While over half of the studies (n = 36) described programs focused almost exclusively on clinical skills acquisition, many (n = 33) specified non-clinical professional development activities. Reflective practice featured to a varying extent in many articles (n = 29). Very few (n = 6) explicitly identified the theoretical basis of their programs. Conclusions Although the literature about in-service nurse mentoring comes mostly from small programs in high-income countries, the largest nurse mentoring programs in the world are in low- and middle-income countries. Much can be learned from studying these programs in greater detail. Future research should analyze key features of programs to make models of mentoring more transparent and translatable. If carefully designed and flexibly implemented, in-service nurse mentoring represents an exciting avenue for enhancing the role of nurses and midwives in people-centered health system strengthening. The contents in this article are those of the authors and do not necessarily reflect the view of the U.S. President's Emergency Plan for AIDS Relief, the U.S. Agency for International Development or the U.S. Government.